Unen-unen sebagai Refleksi Etika Jawa dalam Karawitan Gaya Surakarta - Utomo, Tri Duto; Hardyanto, Hardyanto (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2021)
Unen-unen related to the karawitan (Javenese traditional musical art) comes from the utterances of artists or karawitan observers.In addition, it is also the extent to those unen-unen that reflect Javanese ethics are implemented in social life. This research aimsto describe the form of unen-unen that reflects Javanese ethics in the Surakarta-style karawitan and its implementation in life.The approach used in this research is a qualitative descriptive approach. The data were collected through of observation techniques,unguided interview techniques, recording techniques, observation methods, documentation methods, and note taking techniques.The data were analyzed by content review techniques or content analysis. The results of this study are: (1) the form of unen-unenthat reflects Javanese ethics in the Surakarta-style karawitan classified based on the lingual unit of the word 23 unen-unen,consisting of monomorphemic 14 unen-unen, and polymorphemic 9 unen-unen (3 in the form of compound words); (2) theimplementation of unen-unen that reflects Javanese ethics in the Surakarta-style karawitan could be occured since there is ananalogy between its meaning in society and in the karawitan musical arts. The analogy reffered to the similarity meaning of theunen-unen that is in the karawitan musical arts and that applies in social life, while the implementation is in the form of anactivity example or a concrete form that reflects the found of unen-unen. After being analogized in social life, these unen-unencontain ethics that are often used by Javanese people as a guideline in their lives, therefore Javanese people could achieve aharmonious life and a high spiritual level. Keywords: unen-unen; Javanese ethics; Surakarta-style karawitan